2018
DOI: 10.1080/13603116.2018.1464069
|View full text |Cite
|
Sign up to set email alerts
|

Dancing towards belonging: the use of a dance intervention to influence migrant pupils’ sense of belonging in school

Abstract: With growing hostility towards migrants in the UK, it is ever more important for schools to promote cohesion and wellbeing amongst their diverse pupils. Research has shown the influence of dance interventions on positive psychological and physical wellbeing. The aim of this study was to examine whether dance might influence the wellbeing of migrant pupils, in particular their sense of belonging, given evidence linking this basic human need to positive educational outcomes. Migrant secondary school pupils took … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Recent years have seen much research into how musical participation may mediate experiences of belonging in new settings, with music conceived as a means of welcome and inclusion for migrant children (for instance Crawford, 2017; Gustavsson & Ehrlin, 2018; Kenny, 2018; Marsh & Dieckmann, 2017; Ritchie & Gaulter, 2020; Skidmore, 2016). Approaches to the role of music education in meeting cultural diversity in schools over the past decades have drawn on principles of, for instance, multicultural education (e.g.…”
Section: Background and Previous Researchmentioning
confidence: 99%
“…Recent years have seen much research into how musical participation may mediate experiences of belonging in new settings, with music conceived as a means of welcome and inclusion for migrant children (for instance Crawford, 2017; Gustavsson & Ehrlin, 2018; Kenny, 2018; Marsh & Dieckmann, 2017; Ritchie & Gaulter, 2020; Skidmore, 2016). Approaches to the role of music education in meeting cultural diversity in schools over the past decades have drawn on principles of, for instance, multicultural education (e.g.…”
Section: Background and Previous Researchmentioning
confidence: 99%
“…Issues of social exclusion and belonging also vex other cultural fields such as community arts (Stickley, 2010), cultural festivals (Jaeger & Mykletun, 2013), dance (Gard, 2003; Ritchie & Gaulter, 2020), music (Daenekindt, 2019; Gonzales, 2017; Negus, 2002), and theater (Johnson, 2019; Lee & Finney, 2005). The People Fit and Place factors of our survey may be directly applicable to those settings.…”
Section: Discussionmentioning
confidence: 99%
“…Building trust between practitioners and young people. Most authors highlighted the importance of establishing mutual trust and respect between arts practitioners and CYP to facilitate engagement in the PAB programme (Atkinson & Robson, 2012;Cal o et al, 2020;Clennon & Boehm, 2014;Daykin et al, 2017;Ennis & Tonkin, 2018;Hanrahan & Banerjee, 2017;Parker et al, 2018;Ritchie & Gaulter, 2020). Several described this as a fundamental contextual characteristic when vulnerable and marginalised young people are involved (Cal o et al, 2020;Clennon & Boehm, 2014;Daykin et al, 2017;Hanrahan & Banerjee, 2017), who are suspicious of adults and authority (Clennon & Boehm, 2014), or who have had many experiences of being 'let down' in the past (Hanrahan & Banerjee, 2017).…”
Section: • • •mentioning
confidence: 99%
“…Conversely, where these differ markedly this presented barriers to establishing mutual rapport and trust (Daykin et al, 2017). The creation of mutual trust and respect between arts practitioners and youth beneficiaries of PAB programmes was linked to CYP feeling 'safe ' and protected (Cal o et al, 2020;Clennon & Boehm, 2014;Daykin et al, 2017;Ennis & Tonkin, 2018;Hanrahan & Banerjee, 2017;Parker et al, 2018;Ritchie & Gaulter, 2020). Cal o et al (2020, Hanrahan andBanerjee (2017), andParker et al (2018) all reported that this, in turn, resulted in better connectedness with the programme, constituting another pathway to engagement.…”
Section: • • •mentioning
confidence: 99%
See 1 more Smart Citation